Understanding the Impact of Expertise in Joint and Solo-Improvisation - Issartel, Johann; Gueugnon, Mathieu; Marin, Ludovic (Frontiers in Psychology, 2017)
Joint-improvisation is not only an open-ended creative action that two or more people perform together in the context of an artistic performance (e.g. theatre, music or dance). Joint-improvisation also takes place in daily life activities when humans take part in collective performance such as toddlers at play or adults engaged in a conversation. In the context of this article, joint-improvisation has been looked at from a social motor coordination perspective. In the literature, the nature of the social motor coordination characteristics of joint-improvisation for either the creative aspect or daily-life features of this motor performance remains unclear. Additionally, both solo-improvisation and joint-improvisation need to be studied conjointly to establish the influence of the social element of improvisation in the emergence of multi-agent motor coordination. In order to better understand those two types of improvisation, we compared three level of expertise – novice, intermediate and professional in dance improvisation. Pairs of the same level were asked to improvise together. Each individual was also asked to perform an improvisation on his/her own. We found that each of the three groups present specific movement organisation with movement complexity increasing with the level of expertise. Experts performed shorter movement duration in conjunction with an increase range of movement. The direct comparison of individual and paired conditions highlighted that the joint-improvisation reduced the complexity of the movement organisation and those for all three levels while maintaining the differences between the groups. This direct comparison amongst those three distinct expert groups provides an original insight onto the nature of movement patterns in joint-improvisation situation. Overall, it reveals the role of both individual and collective properties in the emergence of social coordination.